RIBA AND ISLAMIC BANKING, EXAMINING THE PRACTICES OF JAIZ BANK PLC, NIGERIA - abdulmajeed bolade hassan-bello (AHKAM : Jurnal Ilmu Syariah, 2018)
Critics of Islamic banking argue, that how could Islamic banking work when interest (riba) is prohibited? Those in favour argue that Islamic banks can operate without interest. This is the contention of the paper. Islamic bank is a banking which operates without the norm of interest. However, the Muslim scholars have never seriously discussed the three basic questions. Riba, interest, are riba and interest synonymous. The most common application of riba is on monetary transaction relating to “loans” and “credits”. A unique feature of Islamic banking is its profit-and-loss sharing (PLS) paradigm, which is predominantly based on the mudarabah (profit-sharing) and musharaka (joint venture) concepts of Islamic contracting. However, Islamic banks are also criticized for not applying the principle of mudaraba in an acceptable manner. Where banks are eager to take part in profit-sharing but they have little tolerance for risk. Jaiz bank plc, the first Islamic bank in Nigeria, is a quoted public company owned by over 26,000 shareholders. Based on recommendations from Islamic Development Bank (IDB), which is also a shareholder of the bank, Jaiz Bank PLC had partnered with Islamic Bank of Bangladesh (IBBL). However, the Islamic Banks, generally, seem to attract a fraction of the business of financial transactions in any country where conventional banks operate. The challenge facing Islamic banks is the diversity of opinion among the Sharia scholars. Whether the particular practice or product, is Sharia compliant. The paper therefore, concludes that, by prohibition of riba, Islam wishes to establish an economic system where all forms of exploitation are eliminated. The difficulty to understand the prohibition comes from lack of appreciation of the whole complex of Islamic values.  Thus, the future of Islamic banks depends not only upon investing in new products but also upon the satisfying the faith of the stakeholders.